Biodegradation of the aminopolyphosphonate DTPMP by the cyanobacterium Anabaena variabilis proceeds via a C–P lyase‐independent pathway. (23rd January 2017) - Drzyzga, Damian; Forlani, Giuseppe; Vermander, Jochen; Kafarski, Paweł; Lipok, Jacek
Summary: Cyanobacteria, the only prokaryotes capable of oxygenic photosynthesis, play a major role in carbon, nitrogen and phosphorus global cycling. Under conditions of increased P availability and nutrient loading, some cyanobacteria are capable of blooming, rapidly multiplying and possibly altering the ecological structure of the ecosystem. Because of their ability of using non‐conventional P sources, these microalgae can be used for bioremediation purposes. Under this perspective, the metabolization of the polyphosphonate diethylenetriaminepenta(methylenephosphonic) acid (DTPMP) by the strain CCALA 007 of Anabaena variabilis was investigated using 31 P NMR analysis. Results showed a quantitative breakdown of DTPMP by cell‐free extracts from cyanobacterial cells grown in the absence of any phosphonate. The identification of intermediates and products allowed us to propose a unique and new biodegradation pathway in which the formation of ( N‐ acetylaminomethyl)phosphonic acid represents a key step. This hypothesis was strengthened by the results obtained by incubating cell‐free extracts with pathway intermediates. When Anabaena cultures were grown in the presence of the phosphonate, or phosphorus‐starved before the extraction, significantly higher biodegradation rates were found.